Motion planning of a novel 2-DOF parallel manipulator applied as driving simulator of the wheel loader - Knapczyk, Józef; Tora, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
A novel parallel manipulator with 3 legs (2 actuated by linear actuators and one supporting pillar),which is applied in a wheel loader driving simulator, is proposed in this paper. The roll angle and the pitch angle of the platform are derived in closed-form of functions of the variable lengths of two actuators. The linear velocity and acceleration of the selected point and angular velocity of the moving platform are determined and compared with measurement results obtained in the respective point and in the body of the wheel loader. The differences between the desired and actual actuator displacements are used as feedback to compute how much force to send to the actuators as some function of the servo error. A numerical example with a proposed mechanism as a driving simulator is presented.
Keywords: simulator; wheel loader driving; motion planning